Persistence and downward movement of some selected herbicides in the humid and subhumid tropics - Utulu, S.N.; Akobundu, I.O.; Fayemi, A.A.A. (1986)
The persistence and downward movement of atrazine, metolachlor, fluometuron and pendimethalin under field conditions were studied at Onne in southern Nigeria, representing a humid tropical climate and at Ibadan, representing a humid-subhumid transition zone. Atrazine, fluometuron, and metolachlor were each applied pre-emergence at 3·0 and 6·0 kg/ha while pendimethalin was applied at 2·5 and 5·0 kg/ha. The presence of these herbicides was assessed by bioassay techniques. Atrazine, metolachlor and pendimethalin (at 3·0 kg/ha) were not present at phytotoxic levels in the top soil (0–15 cm depth) in soil samples taken from treated plots at 12 weeks after treatment (12 WAT) in both Ibadan and Onne. Fluometuron at 3·0 kg/ha persisted in the top soil at Ibadan but not at Onne at 12 WAT. Although rainfall increased the leaching of atrazine, metolachlor and fluometuron it did not affect pendimethalin, which remained in the top 5 cm of soil at both locations. Results of this study show that crops sensitive to atrazine, metolachlor and pendimethalin can be safely grown in the humid tropics if they are planted at least 12 weeks after any of these herbicides are used on a tolerant crop species.